A BRIEF SOCIOLOGICAL APPOACH TO THE PRODUCTION CONCERNING RELIGION AT THE ANTHROPOLOGY POST-GRADUATE AT THE FEDERAL UNIVERSITY OF PERNAMBUCO-UFPE - de Medeiros, Bartolomeu Tito Figuerôa; Campos, Roberta Bivar Carneiro (Debates do NER, 2007)
Keywords: history of anthropology, religion and society, Universidade Federal de Pernambuco.